TRANSFORMATION OF CIVIL LAW: UNDERSTANDING AND HISTORY OF CIVIL INTERNATIONAL LAW - Nurianto Rachmad Soepadmo (INJOSEDU: International Journal of Social and Education, 2025)
Civil law transformation includes changes and developments in the civil law system that occur over time. These changes are influenced by various factors, including social, economic, political and technological. The aim of this transformation is to ensure that civil law remains relevant and capable of regulating legal relationships between individuals and entities in an ever-evolving society. Indonesian Civil Law aims to determine which law applies and which courts have authority in civil cases across national borders. The history of Private International Law begins during feudalism in Europe. The transformation of Private International Law occurred in line with changes in the structure of society which increasingly tended towards a territorialistic society throughout Europe. In the Indonesian context, Private International Law has an important role in protecting the rights and interests of Indonesian citizens abroad, facilitating international trade, resolving international disputes, international cooperation, and protecting intellectual property rights.